Total synthesis of natural products using hypervalent iodine reagents - Maertens, Gaëtan; L'Homme, Chloé; Canesi, Sylvain (Frontiers in Chemistry, 2015)
We present a review of natural product syntheses accomplished in our laboratory during the last five years. Each synthetic route features a phenol dearomatization promoted by an environmentally benign hypervalent iodine reagent. The dearomatizations demonstrate the “aromatic ring umpolung” concept, and involve stereoselective remodeling of the inert unsaturations of a phenol into a highly functionalized key intermediate that may contain a quaternary carbon center and a prochiral dienone system. Several new oxidative strategies were employed, including transpositions (1,3-alkyl shift and Prins-pinacol), a polycyclization, an ipso rearrangement, and direct nucleophilic additions at the phenol para position. Several alkaloids, heterocyclic compounds, and a polycyclic core have been achieved, including sceletenone (a serotonin reuptake inhibitor), acetylaspidoalbidine (an antitumor agent), fortucine (antiviral and antitumor), erysotramidine (curare-like effect), platensimycin (an antibiotic), and the main core of a kaurane diterpene (immunosuppressive agent and stimulator of apoptosis). These concise and in some cases enantioselective syntheses effectively demonstrate the importance of hypervalent iodine reagents in the total synthesis of bioactive natural products.